2020
DOI: 10.1002/chem.202004221
|View full text |Cite
|
Sign up to set email alerts
|

The 2‐Amino Group of 8‐Aza‐7‐deaza‐7‐bromopurine‐2,6‐diamine and Purine‐2,6‐diamine as Stabilizer for the Adenine–Thymine Base Pair in Heterochiral DNA with Strands in Anomeric Configuration

Abstract: Stabilization of DNA is beneficial for many applications in the fields of DNA therapeutics, diagnostics, and materials science. Now, this phenomenon is studied on heterochiral DNA, an autonomous DNA recognition system with complementary strands in α‐D and β‐D configuration showing parallel strand orientation. The 12‐mer heterochiral duplexes were constructed from anomeric (α/β‐D) oligonucleotide single‐strands. Purine‐2,6‐diamine and 8‐aza‐7‐deaza‐7‐bromopurine‐2,6‐diamine 2′‐deoxyribonucleosides having the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Various factors contribute to the shape of the CD‐spectra: i) the conformation of the monomers which can be syn or anti , ii) the conformation of the sugar residues ( N vs. S ), iii) the hydrogen‐bonding network formed between nucleobases, iv) stacking interactions between nucleobases or base pairs and v) the helicity of the duplex (+ or −). Previous CD experiments have shown that CD spectra of α‐anomeric single strands display spectra with mirror‐like Cotton effects with respect to the β‐strand [1,2,3] . Complete mirror images are not expected as diastereoisomers are compared and not enantiomeric molecules with strands in d ‐ and l ‐configuration.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Various factors contribute to the shape of the CD‐spectra: i) the conformation of the monomers which can be syn or anti , ii) the conformation of the sugar residues ( N vs. S ), iii) the hydrogen‐bonding network formed between nucleobases, iv) stacking interactions between nucleobases or base pairs and v) the helicity of the duplex (+ or −). Previous CD experiments have shown that CD spectra of α‐anomeric single strands display spectra with mirror‐like Cotton effects with respect to the β‐strand [1,2,3] . Complete mirror images are not expected as diastereoisomers are compared and not enantiomeric molecules with strands in d ‐ and l ‐configuration.…”
Section: Resultsmentioning
confidence: 96%
“…Previous CD experiments have shown that CD spectra of α‐anomeric single strands display spectra with mirror‐like Cotton effects with respect to the β‐strand. [ 1 , 2 , 3 ] Complete mirror images are not expected as diastereoisomers are compared and not enantiomeric molecules with strands in d ‐ and l ‐configuration. The phenomenon has been already discussed for nonfunctionalized α‐ d hexamer oligonucleotide duplexes with all‐purine or all‐pyrimidine bases in either the α‐ or the β‐strand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleoside 2 found widespread application as efficient DNA stabilizer without disturbing the DNA double helical structure [8h,10] . The stabilizing properties of 1 and 2 were used to strengthen homochiral and heterochiral DNA and to harmonize the stability of the dA‐dT and dG‐dC base pair [8h,10] . The stabilizers 1 and 2 have been already incorporated in DNA by solid‐phase synthesis employing phosphoramidite chemistry [8h,10,12] .…”
Section: Resultsmentioning
confidence: 99%